analisis sediaan bahan baku tebu menggunakan metode Economic Production Quantity (EPQ) pada proses produksi gula pasir di PT. Sinergi Gula Nusantara - Dandy Wahyu Ali Mashuri; Taufik Setyadi; Nisa Nafi Idhoh Fitriana (Universitas Nahdlatul Ulama Blitar, 2026)
This research aims to analyze the raw material inventory of sugarcane using the Economic Production Quantity (EPQ) method in the sugar production process at PT. Sinergi Gula Nusantara Mojokerto. The objectives of this study are to: (1) analyze the impact of sugarcane raw material inventory on the smoothness of sugar production, (2) determine the optimal economic inventory quantity for daily production, and (3) analyze the cost efficiency of raw material inventory in daily production at PG. Gempolkrep. The data analysis methods used in this study are descriptive analysis and the EPQ method. The results show that the smoothness of production at PG. Gempolkrep is disrupted due to unmet sugarcane raw material needs, caused by the conversion of land use, especially sugarcane farming areas in the Mojokerto region. This leads to an insufficient supply of raw materials for PG. Gempolkrep. Additionally, the EPQ calculation of production quantity shows a significant comparison with the company's policy. The production quantity based on the company's policy is still below the average daily production target of 600 tons per day, while the EPQ calculation results in a production quantity of 600-700 tons per day, which is above the target. This indicates that PG. Gempolkrep is not yet optimal in its production. Regarding production costs, the EPQ method calculation is more efficient than the production costs incurred by PG. Gempolkrep. The average production cost according to PG. Gempolkrep is Rp. 23,785,399, while the EPQ calculation shows Rp. 22,574,245, resulting in cost savings of Rp. 1,211,154. From these calculations, it can be concluded that using the EPQ method is more economical and efficient in managing production costs.